Relationship between Energy Consumption, Economic Growth and Population in Kazakhstan - Parmanova, Rimma; Baimoldayeva, Meruyert; Azretbergenova, Gulmira; Beisekova, Perizat (International Journal of Energy Economics and Policy, 2025)
This study examines the relationship between energy consumption, economic growth and population in Kazakhstan for the period 1991-2023. In the study, the Johansen cointegration test was applied to determine the long-term relationship between the variables and the results show that the variables are cointegrated. The Granger causality test was used to analyze the causality relationships. The findings reveal that there is a unidirectional causality from energy consumption to gross domestic product (GDP). This situation shows that energy consumption is an important factor driving economic growth in the Kazakh economy. In addition, a unidirectional causality relationship from GDP to the population variable was determined. This result shows that economic growth has an effect on population growth but there is no reverse relationship. The findings reveal that Kazakhstan should develop strategies to increase energy efficiency within the framework of sustainable growth policies. In addition, it is recommended to plan long-term development policies by considering the effect of economic growth on population growth. The study emphasizes that the relationship between energy consumption and economic growth should be examined in more depth.